Crystallization behavior and morphological features of ethylene-vinyl alcohol 44 copolymer - Clement Freymond; Alain Guinault; Matthieu Gervais; Miroslaw Pluta; Tomasz Makowski; Ewa Piorkowska; Cyrille Sollogoub (eXPRESS Polymer Letters, 2022)
This work is a first attempt to study the crystallization behavior of ethylene-vinyl alcohol copolymer with 44 mol% of ethylene units (EVOH44) and to observe the supermolecular structures developed during its crystallization. Thermal analysis has evidenced a very fast crystallization and the formation of different crystal populations during isothermal crystallization. In-situ wide-angle X-ray scattering experiments using a synchrotron radiation source have shown a unique orthorhombic morphology, independently of the crystallization conditions. Small spherulites (with an average radius of about 1 μm) were observed using polarized optical microscopy and confirmed by typical four-leaf patterns obtained by small-angle light scattering. In-situ atomic force microscopy has revealed stacked lamellae growing from common centers to form small spherulitic entities. Finally, studies of isothermal crystallization have evidenced the existence of partial crystallization (especially at high crystallization temperatures) and the need for higher undercooling to complete crystallization.